Talking about sexual assault: society's response to survivors - Ullman, Sarah E. (Psychology of women book series)
The social context of talking about sexual assault -- Theories of rape and women's disclosure -- Why, how often, and to whom do women disclose, and what factors influence whether disclosure is healing? -- Social reactions and their effects on survivors -- Advocates and clinicians' experiences helping survivors -- Conducting interviews with sexual assault survivors -- Challenging the rape culture : recommendations for change